2014
DOI: 10.1111/vru.12148
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Noncontrast Computed Tomography and High‐field Magnetic Resonance Imaging in the Evaluation of Great Danes With Cervical Spondylomyelopathy

Abstract: Computed tomography (CT) provides excellent bony detail, whereas magnetic resonance (MR) imaging is superior in evaluating the neural structures. The purpose of this prospective study was to assess interobserver and intermethod agreement in the evaluation of cervical vertebral column morphology and lesion severity in Great Danes with cervical spondylomyelopathy by use of noncontrast CT and high-field MR imaging. Fifteen client-owned affected Great Danes were enrolled. All dogs underwent noncontrast CT under se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 28 publications
(59 reference statements)
2
16
1
Order By: Relevance
“…However, our results indicated that the vertebral foraminal width varied significantly based on angle acquisition at only the cranial vertebral locations. In general, Great Danes with cervical spondylomyelopathy most often suffer from bilateral compressions in the lateral or dorsolateral direction . In the population of Great Danes enrolled in this study, the lateral compressions more greatly affected the cranial aspect of the vertebrae, explaining why our results differed from the results obtained from osteological studies of the cervical vertebrae of Great Danes .…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…However, our results indicated that the vertebral foraminal width varied significantly based on angle acquisition at only the cranial vertebral locations. In general, Great Danes with cervical spondylomyelopathy most often suffer from bilateral compressions in the lateral or dorsolateral direction . In the population of Great Danes enrolled in this study, the lateral compressions more greatly affected the cranial aspect of the vertebrae, explaining why our results differed from the results obtained from osteological studies of the cervical vertebrae of Great Danes .…”
Section: Discussioncontrasting
confidence: 84%
“…Our results also showed that the width of the vertebral foramina in Great Danes with cervical spondylomyelopathy was significantly narrower than that of the control dogs, regardless of the angle of image acquisition. Considering that Great Danes with cervical spondylomyelopathy most often suffer from lateral or dorsolateral compressions, it is not surprising to find that the CT measurements of affected dogs obtained in this study also showed that their vertebral foramina are laterally narrowed when compared to the control group …”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Bony malformations and osteoarthritic changes of the articular process joints, pedicles, and dorsal lamina are common in dogs with osseous‐associated CSM . In our study, magnetic resonance imaging confirmed the presence of osseous‐associated CSM in all affected dogs, with lateral and dorsolateral spinal cord compression secondary to OA involving the articular process joints, pedicles, or both, present in all dogs.…”
Section: Discussionsupporting
confidence: 75%
“…This dog was a 2.5‐year‐old female spayed Great Dane with the following CSF results: 219 RBC/μL, 1 WBC/μL, and protein concentration of 12.1 mg/dL. All dogs included in our study were classified as clinically normal based on complete neurologic examination and MRI of the cervical vertebral column (considered the gold standard for diagnosis of OA‐CSM), but it is possible that this dog may have been asymptomatic or had early onset or dynamic OA‐CSM in the absence of detectable imaging changes . Asymptomatic OA‐CSM is recognized in people, horses, and dogs, and has been described in Doberman Pinschers with DA‐CSM and reported in Great Danes with OA‐CSM .…”
Section: Discussionmentioning
confidence: 99%